2012
DOI: 10.1097/mcp.0b013e32834db10d
|View full text |Cite
|
Sign up to set email alerts
|

The indoor air and asthma

Abstract: Purpose of review The objective is to discuss recent progress in our understanding of the role of the indoor environment in asthma, focusing on the special role of cat allergens. Recent findings Sensitization to Fel d 1 is the dominant event in inhalant responses to cat; however, there are also IgE responses to the lipocalin (Fel d 4), to cat albumin (Fel d 2), and to the oligosaccharide galactose-alpha-1,3-galactose (alpha-gal) on cat IgA (Fel d 5w) and other molecules. The dose response and routes of sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…The allergic response to pets in humans, that is, to hair of pets, is known to be one of the most challenging issues in the modern allergy science [ 14 , 15 , 17 20 ]. Allergens of cats are the best studied types [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The allergic response to pets in humans, that is, to hair of pets, is known to be one of the most challenging issues in the modern allergy science [ 14 , 15 , 17 20 ]. Allergens of cats are the best studied types [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, pet allergens were found not only in families with pets, but also in those without pets, and in public places, including communities and schools. 24 Thus, the exact aeroallergen to be avoided was difficult to identify. Specific immunotherapy (SIT) is the only disease-modifying treatment for AR, 25 and previous studies have reported that this treatment is clinically effective in desensitisation to pet allergens.…”
Section: Discussionmentioning
confidence: 99%
“…in asthmatics were observed in the further analyses. These observations suggest that patients with asthma may have allergies to different environmental allergens such as cockroaches and pet allergens [39], [40], as well as house dust mites.…”
Section: Discussionmentioning
confidence: 94%